2021
DOI: 10.5114/pq.2020.100280
|View full text |Cite
|
Sign up to set email alerts
|

Trunk and hip muscles activation patterns in subjects with and without chronic low back pain: a systematic review

Abstract: The purpose of this study was to determine normal and abnormal patterns of activation of gluteus maximus (GM), hamstring (HAM), contralateral erector spinae (CES), and ipsilateral erector spinae (iES) muscles during a prone hip extension test in healthy or asymptomatic subjects and those with non-specific chronic low back pain through a systematic review. Studies were recognized by searching electronic databases (Embase, MEdLiNE/PubMed, Cochrane Library, PEdro [Physiotherapy Evidence database], and CiNAHL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It was found that people with LBP did not differ from asymptomatic people with regard to the angle of lumbar lordosis or the angle of the anterior tilt of the pelvis in a standing position although they did show differentiation in terms of the range of motion of the lumbar spine in all directions, the velocity of movement of this section, and worsened proprioception during movement reposition [ 39 ]. These observations emphasise the disturbances in the motor function of the lumbar spine [ 40 ] rather than changes in the shape of the anterior-posterior curves in people with the LBP. The presented study confirms that the lumbosacral angle did not differentiate between the study groups.…”
Section: Discussionmentioning
confidence: 96%
“…It was found that people with LBP did not differ from asymptomatic people with regard to the angle of lumbar lordosis or the angle of the anterior tilt of the pelvis in a standing position although they did show differentiation in terms of the range of motion of the lumbar spine in all directions, the velocity of movement of this section, and worsened proprioception during movement reposition [ 39 ]. These observations emphasise the disturbances in the motor function of the lumbar spine [ 40 ] rather than changes in the shape of the anterior-posterior curves in people with the LBP. The presented study confirms that the lumbosacral angle did not differentiate between the study groups.…”
Section: Discussionmentioning
confidence: 96%
“…During diverse functional tasks, LBP is related to trunk kinematics and muscle activation (Hemming et al, 2019). A study has shown that patients with CLBP had delayed activation of deep abdomen and back muscles and increased activation of superficial trunk muscles (Kamel et al, 2021).…”
Section: Core Muscle Activationmentioning
confidence: 99%